Expert System Logika Fuzzy Penentuan Proses Penanaman Bibit Unggul Kayu Manis dengan Metode Mamdani - Silvilestari, Silvilestari (Building of Informatics, Technology and Science (BITS), 2021)
Cinnamon is a plant that many people are interested in because cinnamon has a high selling value. Cinnamon has two advantages when it grows big, namely the bark and the wood can be marketed at a high price. Currently, many people are friends with cinnamon to support future needs. The problem of this research is the lack of information and understanding of the community in choosing cinnamon that is suitable for planting so that it thrives and has good quality. The purpose of this research is to help the community in choosing good seeds for planting. The settlement of this case uses the expert method of Mamdani, the process of solving the Mamdani method uses the OR operator. The working process of the Mamdani method is fuzification, inference engine, application of implication functions and the last is defuzification. With the decision-making system in selecting superior cinnamon seeds, it is hoped that it can help and facilitate the community in making decisions in choosing superior seeds with more accurate results. The results of this study are in the form of a prototype with the input process in the form of planting land, cinnamon seeds, the process of planting shoots, and maintaining cinnamon as output in the form of decisions, namely Very Satisfactory, Satisfactory and Unsatisfactory